Between the Teacher-Translator (TT) and the Officer-Translator (OT): The Useful but Elusive Handshake? - Tunde Ajiboye (Yoruba Studies Review)
This essay is out to draw attention to a simple but often overlooked subject: the need to recognize two broad streams of translators and, more importantly, to draw together not only for the mutual benefit of both streams but for the ultimate growth and sustenance of the enterprise as a social cum international service. The essay admits the classic definition of translation and puts its major plank of argument on the assumption that translation and interpretation are Siamese twins. It purports that so much is going on in classroom translation that without it, office translation may well be a mirage. Put more sharply, classroom translation often called pedagogical translation is the father of office translation. Yet there is little, except for conferences, which brings the two into cross-fertilizing synergy. This is against the backdrop that office translation as an activity carried out for a fee or in return for a specified honorarium or salary. The central argument is that, whereas the teacher-translator is the indispensable light to the officer-translator, he is not open to being readily outsourced and that, unless regular occasions are provided for the teacher-translator to pull his weight in the field, the assumed parity between both streams might be a nullity.